2015
DOI: 10.1017/s1368980015000828
|View full text |Cite
|
Sign up to set email alerts
|

Breast-feeding and postpartum weight retention: a systematic review and meta-analysis

Abstract: Objective: Weight gained during pregnancy and postpartum weight retention might contribute to obesity in women of childbearing age. Whether breast-feeding (BF) may decrease postpartum weight retention (PPWR) is still controversial. The purpose of our systematic review and meta-analysis was to investigate the relationship between BF and PPWR. Design: Three databases were systematically reviewed and the reference lists of relevant articles were checked. Meta-analysis was performed to quantify the pooled standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 57 publications
2
32
0
5
Order By: Relevance
“…The results of the present study suggest that, compared with exclusive formula feeding or a combination of breast and formula feeding, exclusive breastfeeding for the first month postpartum leads to an earlier return to pre-pregnancy weight at both 1 and 6 months postpartum. Thus, we contend that exclusive breastfeeding has a protective effect on PPWR, which is supported by the findings of several previous studies [5,6,21,23]. …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the present study suggest that, compared with exclusive formula feeding or a combination of breast and formula feeding, exclusive breastfeeding for the first month postpartum leads to an earlier return to pre-pregnancy weight at both 1 and 6 months postpartum. Thus, we contend that exclusive breastfeeding has a protective effect on PPWR, which is supported by the findings of several previous studies [5,6,21,23]. …”
Section: Discussionsupporting
confidence: 90%
“…A review published in 2015 indicated that, compared with formula feeding, continual breastfeeding for 3-6 months correlates negatively with PPWR; however, the difference becomes nonsignificant after 6 months [21]. The results of the present study suggest that, compared with exclusive formula feeding or a combination of breast and formula feeding, exclusive breastfeeding for the first month postpartum leads to an earlier return to pre-pregnancy weight at both 1 and 6 months postpartum.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Interestingly and unexpectedly, the PWC did not significantly differ between the HIB and non‐HIB groups in our study. Similarly, some authors reported that there was no significant effect of breastfeeding on the PWC from 1 to 3 months post‐partum . Although breastfeeding for 3 to 6 months may decrease post‐partum weight retention compared with formula feeding, its efficacy remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…There is uncertainty about the impact of breastfeeding on postpartum weight. Systematic reviews and meta‐analyses have found no association or a modest benefit of breastfeeding on postpartum weight . The most recent meta‐analysis found postpartum weight retention 0.38 (95% CI, 0.11‐ 0.6) kg lower in breastfeeding compared with bottle feeding mothers .…”
Section: The Role Of Diet and Pa In Weight Gainmentioning
confidence: 99%